Ultrafine nanoporous aluminum by electrolytic dealloying of aluminum-magnesium alloys in glyme-based electrolytes with recovery of sacrificial magnesium. (December 2022) - Lee, Timothy; Koh, Hyeongjun; Ng, Alexander K.; Liu, Jiaxin; Stach, Eric A.; Detsi, Eric
Abstract: Air-free electrolytic dealloying using non-aqueous electrolytes is a sustainable method for creating nanoporous Al (NP-Al) with highly reactive nanoscale-sized ligaments from Al-Mg parent alloys while simultaneously recovering the sacrificial Mg. However, this synthesis strategy is limited in versatility by the low number of available non-aqueous electrolytes that can conduct Mg ions and has so far only been proven to work with all-phenyl complex (APC) electrolyte derived from in situ reaction between two equivalents of Lewis base C₆H₅ClMg and one equivalent of Lewis acid AlCl3 in tetrahydrofuran (THF) solvent. Here we demonstrated that a new electrolyte consisting of MgCl2 /AlCl3 /Mg(TFSI)2 (or MACT) in glyme-based solvents recently introduced in the Mg-ion battery community can also be used to create NP-Al. This alternative electrolyte exhibits higher electrochemical performance than APC and can create ultrafine NP-Al with ≈ 6–14 nm ligament size, which is smaller than the ≈ 10–20 nm ligament size commonly achieved using APC. Graphical abstract: Image, graphical abstract